2013
DOI: 10.1177/0098628313487423
|View full text |Cite
|
Sign up to set email alerts
|

Student Grade Expectations at Technical College, 2-, and 4-Year Institutions

Abstract: Although students’ final course grade expectations have been the focus of several studies, none have looked systematically at students’ expectations for grade distributions for the whole class across institutional types, student year in school, and course levels. This study examined such differences as a function of gender, course level, and year in school at a university, community college, and technical college. Participants indicated average grades students should receive in first-year, sophomore and, for u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 11 publications
2
7
0
Order By: Relevance
“…Students expected higher grades during their sophomore year compared with first-year students; however, university students expected much lower grades for both compared with students at technical colleges and 2-yr institutions (36). Women on average tended to expect higher grades for all course levels compared with men (36).…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…Students expected higher grades during their sophomore year compared with first-year students; however, university students expected much lower grades for both compared with students at technical colleges and 2-yr institutions (36). Women on average tended to expect higher grades for all course levels compared with men (36).…”
mentioning
confidence: 89%
“…In addition to motivation, previous studies (25,26,36,49,55) have suggested that students' performance in class is correlated with students' estimation of grades. On the first day of an introductory biology class, 90% of students believed they would earn an A or a B (25), whereas other students expected to score 81.67 points on the final examinations but only earned 76.12 points (averaged) (49).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, some teachers using the Rating System consider that the idea of competitiveness makes the framework of the system itself. Therefore, considering that the phenomenon of motivation is connected with a number of factors which induce a person to work (that is motivate a student to study) [3,4], we decided to measure the motivating power of the Rating System indirectly -through the factors inspiring such motivation. Competitiveness in educational environment is traditionally considered as contributing to progress of students.…”
Section: Resultsmentioning
confidence: 99%
“…Tests would include main effects as well as the potential for an interaction between the two factors. For example, in a mixed-design study of student grade expectations over the years in school between technical, two-year, and fouryear institutions, McCann et al (2013) found significance over the years in school as well as between types of institutions. Specifically, one of their NEW DIRECTIONS FOR TEACHING AND LEARNING • DOI: 10.1002/tl findings was that expected sophomore grades were significantly higher than expected first-year grades (repeated-measures), and expected grades at the four-year institutions were significantly lower than at the two-year institutions (between-groups;McCann et al 2013).…”
Section: Repeated-measures Designmentioning
confidence: 99%